Exploring characteristics and severity of road traffic injuries in Lebanon using emergency department hospital-based data - Dalal Youssef; Pascale Salameh; Walid Al-Shaar; Nada Ghosn; Louis-Rachid Salmi (Scientific Reports)
Abstract In Lebanon, the lack of quality data on road traffic injuries (RTIs) led to the implementation of a hospital-based RTI surveillance system by the Ministry of Health in in private and public-run hospitals in the Bekaa governorate. This paper aims to describe the characteristics and severity of RTIs recorded over two years during the pilot phase. It also assesses the strengths and challenges of the surveillance system, highlighting areas for enhancement. The data collected from the Emergency department (ED) was used to conduct a retrospective analysis of population-based injuries hospitalized for road traffic crashes (RTC). Designated focal persons reported injuries weekly using a standardized form, which included demographic and crash-related variables, body lesions, and vital signs. Data were coded per the International Classification of Diseases (ICD-10), entered into Epidata, and analyzed using SPSS. The RTI surveillance system was assessed using Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. Over two years, a total of 1576 cases of RTIs were reported. The male-to-female ratio was 2.16 and the majority of RTIs (44.4%) were recorded among those aged between 15 and 29 years old. From 2013 to 2015, a decrease of 0.7% in the revised trauma score (RTS < 4) was recorded. On the contrary, an increase of 3.9% in injury severity score (ISS) that ranged between 15 and 75 was reported. The probability of survival of an injured individual at one month was improved. The hospital-based surveillance system demonstrated strengths in structured data collection and ethical considerations but faced challenges like underreporting, limited coverage, and resource constraints. Recommendations for improvement include enhancing data quality and timely reporting, ultimately supporting evidence-based road safety interventions.